Pseudarthrosis of a calcaneus fracture: a case report - Karakurt, Lokman; Yilmaz, Erhan; Belhan, Oktay; Incesu, Mustafa; Serin, Erhan (My University, 2004)
Nonunion after a calcaneus fracture is rare. A forty-two-year-old man presented with complaints of extreme left heel pain on weight-bearing, that required him to use crutches. Clinical and radiological studies yielded a diagnosis of calcaneal nonunion. He had a history of an open calcaneal fracture that occurred in a traffic accident eight months before, for which he received cast treatment. He underwent surgical treatment (curettage, bone graft, and internal fixation) for the nonunion of the calcaneus. Eight months after the operation, no problem was observed at the union site, and the patient returned to his normal activity levels. He had a slight heel pain appearing only after walking long distances, which was attributed to the subtalar joint.
Kalkaneus kiriginda psödoartroz: olgu sunumu.
Keywords: Adult; Calcaneus; Diagnosis, Differential; Fracture Fixation, Internal; Humans; Male; Pseudarthrosis; adult; article; calcaneus; case report; differential diagnosis; human; injury; male; osteosynthesis; pseudarthrosis; radiography